Workplace violence against healthcare professionals in a multiethnic area: a cross-sectional study in southwest China - Ying Wang; Qunhong Wu; Mingli Jiao; Kexin Jiang; Huiying Fang; Yameng Wang; Haonan Jia; Ruohui Chen; Lifeng Wei; Gangyu Zhang; Yuanheng Li; Jingqun Li; et al. (BMJ Open)
Objective The purpose of this study is to examine workplace violence (WPV) towards healthcare professionals in a multiethnic area in China, including prevalence, influencing factors, healthcare professionals’ response to WPV, expected antiviolence training measures and content, and evaluation of WPV interventions.Design A cross-sectional study.Setting A grade III, class A hospital in the capital of Yunnan Province, which is the province with the most diverse ethnic minority groups in China.Participants In total, 2036 healthcare professionals participated, with a response rate of 83.79%.Results The prevalence of physical and psychological violence was 5.5% and 43.7%, respectively. Healthcare professionals of ethnic minority were more likely to experience psychological violence (OR=1.54, 95% CI 1.16 to 2.05). Stratified by gender, male healthcare professionals of ethnic minority suffered from more physical violence (OR=3.31, 95% CI 1.12 to 9.79), while female healthcare professionals suffered from psychological violence (OR=1.71, 95% CI 1.24 to 2.36). We also found a unique work situation in China: overtime duty on-call work (18:00–07:00) was a risk factor for psychological violence (OR=1.40, 95% CI 1.02 to 1.93). Healthcare professionals of ethnic minority are less likely to order perpetrators to stop or to report to superiors when faced with psychological violence. They are also more interested in receiving training in force skills and self-defence. Both Han and ethnic minority participants considered security measures as the most useful intervention, while changing the time of shift the most useless one.Conclusion Our study comprehensively described WPV towards healthcare professionals in a multiethnic minority area. More research on WPV conducted in multiethnic areas is needed.